The effectiveness of combining a home-based Digital motor Telerehabilitation program with conventional therapy in progressive multiple sclerosis: A study protocol for a multicenter, randomized controlled trial - Marialuisa Gandolfi; Mauro Crestani; Gabriele Perachiotti; Francesca Salaorni; Andrea Baroni; Alberto Gajofatto; Riccardo Orlandi; Michela Rimondini; Valeria Donisi; Stefano Landi; Giovanni Morone; Mirta Fiorio; et al. (Digital Health)
Objective The primary aim is to evaluate the effectiveness of in-hospital rehabilitation followed by a home-based Digital Telerehabilitation program on mobility versus in-hospital rehabilitation alone in patients with Progressive Multiple Sclerosis. Secondary aims are the intervention's impact on clinical, physiological, psychological, and economic outcomes. Methods This multicenter, single-blind, randomized controlled trial will involve 78 participants with Progressive Multiple Sclerosis. All participants will complete 10 in-hospital rehabilitation sessions (1 hour/day, three days/week). The experimental group will receive an additional 12-week home-based Digital Telerehabilitation (3 sessions/week), while the control group general self-management instructions. Based on primary and secondary outcomes, a blinded rater will evaluate participants before and after rehabilitation and at 12 and 24 weeks follow-up. Results Integrating home-based Digital Telerehabilitation is expected to mitigate the progression of disability, promote self-management, and reduce healthcare costs, offering a cost-effective and accessible solution for managing Progressive Multiple Sclerosis. Conclusions This study will provide essential insights into the role of Digital Telerehabilitation in the hybrid care model to manage Progressive Multiple Sclerosis, with the potential to guide clinical practice and inform health policy. The physiological and economic evaluations will further clarify the benefits and cost-effectiveness of the intervention. Trial registration This trial was registered in ClinicalTrials.gov (NCT06485115; URL: https://clinicaltrials.gov/study/NCT06485115?cond=NCT06485115&rank=1 ).